Analisis Kinerja Pegawai Pada Kantor Desa Bontolangkasa Utara Kecamatan Bontonompo Kabupaten Gowa: Penelitian - Muhammad Arfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Employee performance is a key factor in determining the success of village governance, particularly in providing effective, efficient, and accountable public services. This study aims to determine employee performance at the North Bontolangasa Village Office, Bontonompo District, Gowa Regency. This study used a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing methods. The results indicate that the performance of North Bontolangasa Village employees is generally quite good, as evidenced by their ability to carry out administrative tasks, financial management, and public services. However, several obstacles remain that impact performance, including low employee discipline, limited work facilities and infrastructure, and minimal use of information technology in village administration. The study concludes that strategies to improve employee performance include improving employee discipline and motivation, providing adequate facilities and infrastructure, and training in the use of information technology in administration and public services.